Pathogenicity of Heterorhabditis bacteriophora in ultraviolet light–irradiated agar suspension on Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae - Pérez Tesén, Edgar Darwin; Rodas Adrianzén, Jennifher Elizabeth; Chávez Cabrera, Alexander; Neira de Perales, María Elena (Georgia Entomological Society, 2023)
Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is an economically important pest of variety of crops, including maize (Zea mays L.), rice (Oryza sativa L.), and cotton (Gossypium spp.). Conventional chemical insecticides are usually used for management of this pest; however, a viable alternative is the use of microbial agents or their biological products, such as entomopathogenic nematodes. Their efficacy, however, is affected by abiotic conditions including ultraviolet (UV) light and desiccation. It is therefore necessary to develop formulations that preserve or extend the viability of the agent or product while facilitating ease of application. This laboratory study was conducted to determine the pathogenicity of the nematode Heterorhabditis bacteriophora (Poinar) against S. frugiperda third-instar larvae. Infective juveniles (IJs) of the nematode were tested at a concentration of 350 IJs/ml in two substrates (water and 0.1% [w/v] agar suspension) with four periods of exposure (0, 5, 10 and 15 min) to UV radiation at 253.7 nm. Each of the eight treatments included 40 larvae, with each treatment replicated three times in a completely randomized design (two factors of type of medium and UV exposure time). We determined that the 0.1% (w/v) agar suspension, compared with the water substrate, protected the IJs from harmful UV light and thus improved the survival and pathogenicity of the IJs against third-instar S. frugiperda.